PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS MEDIA ANIMASI INTERAKTIF UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS X DI SMK PENERBANGAN TECHNO TERAPAN MAKASSAR - Mulyati Mulyati; Fardinah Fardinah (STKIP Paris Barantai, 2019)
This type of research is Research and Development (Research and Development) which aims to improve student learning outcomes in mathematics especially Geometry material through the development of interactive animation-based learning media by adapting the development model of Tiagarajah known as 4 D namely define, design, design, develop (dissemination) and disseminate. This research was conducted at the Makassar Applied Techno Vocational School in 2018/2019 academic year, and the research subjects were Grade X students. The results showed that the learning media based on interactive animation media showed highly valid criteria with a validity value of 3.59, the effectiveness of learning using interactive animation media mathematics learning obtained a percentage of 91.75% and the effectiveness of interactive animation media based on mathematics learning outcomes showed the percentage classical completeness reaches 83%, so it can be said that the interactive animation media developed meets valid and effective criteria. Keywords: Animation media, motivation questionnaire, Learning Outcomes